The Proteomic Composition and Organization of Constitutive Heterochromatin in Mouse Tissues - Schmidt, Annika; Zhang, Hui; Schmitt, Stephanie; Rausch, Cathia; Popp, Oliver; Chen, Jiaxuan; Cmarko, Dusan; Butter, Falk; Dittmar, Gunnar; Lermyte, Frederik; Cardoso, M Cristina (Cells, 2024)
Pericentric heterochromatin (PCH) forms spatio-temporarily distinct compartments and affects chromosome organization and stability. Albeit some of its components are known, an elucidation of its proteome and how it differs between tissues in vivo is lacking. Here, we find that PCH compartments are dynamically organized in a tissue-specific manner, possibly reflecting compositional differences. As the mouse brain and liver exhibit very different PCH architecture, we isolated native PCH fractions from these tissues, analyzed their protein compositions using quantitative mass spectrometry, and compared them to identify common and tissue-specific PCH proteins. In addition to heterochromatin-enriched proteins, the PCH proteome includes RNA/transcription and membrane-related proteins, which showed lower abundance than PCH-enriched proteins. Thus, we applied a cut-off of PCH-unspecific candidates based on their abundance and validated PCH-enriched proteins. Amongst the hits, MeCP2 was classified into brain PCH-enriched proteins, while linker histone H1 was not. We found that H1 and MeCP2 compete to bind to PCH and regulate PCH organization in opposite ways. Altogether, our workflow of unbiased PCH isolation, quantitative mass spectrometry, and validation-based analysis allowed the identification of proteins that are common and tissue-specifically enriched at PCH. Further investigation of selected hits revealed their opposing role in heterochromatin higher-order architecture in vivo.
Keywords: Animals; Proteome; Membrane Proteins; Proteomics; zvířata; heterochromatin; proteomika; Mice; Heterochromatin; Brain; proteom; membránové proteiny; mozek; myši